2016
DOI: 10.1108/ohi-03-2016-b0020
|View full text |Cite
|
Sign up to set email alerts
|

Application of Media Art Visual Communication Concept in Multi-Scale Control

Abstract: Color is the dominant element of visual communication design. For cities, color is one of their characteristics. Improving the overall style of a city through the control and planning of architectural color has been a hot issue in urban control and planning in recent years. Considering color pollution in urban planning, we analyze the important role of color in visual communication design from the perspective of the visual communication concept of media art. The current situation of residential building colors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Han and Deng focused on new media and visual communication design and analyzed the occurrence of new media and its characteristics of the times. At the same time, the connotation and development process of visual communication design are explained in simple terms, and it is concluded that the change of media technology is the main reason for the evolution of visual communication design [ 19 ].…”
Section: Related Workmentioning
confidence: 99%
“…Han and Deng focused on new media and visual communication design and analyzed the occurrence of new media and its characteristics of the times. At the same time, the connotation and development process of visual communication design are explained in simple terms, and it is concluded that the change of media technology is the main reason for the evolution of visual communication design [ 19 ].…”
Section: Related Workmentioning
confidence: 99%
“…In the traditional art of integrated media communication, we should not only integrate the respective advantages of traditional media and emerging media but also make full use of modern digital production and information transmission technology [4]. On this basis, we should actively try the innovative expression of traditional art, deeply excavate its inherent cultural essence, and strive to expand its effective path in integrated media communication [5].…”
Section: Introductionmentioning
confidence: 99%